Risk of falls, vestibular multimodal processing, and multisensory integration decline in the elderly–Predictive role of the functional head impulse test - Politi, Leandro; Salerni, Lorenzo; Bubbico, Luciano; Ferretti, Fabio; Carucci, Mario; Rubegni, Giovanni; Mandalà, Marco (Frontiers in Neurology, 2022)
Age-related degeneration of the vestibular system, also known as presbyastasis, leads to unstable gait and higher risk of falls. These conditions affect lifestyle and may have non-negligible social repercussions due to fear-related states of anxiety and depression. In order to develop a model for predicting risk of falls, we assessed vestibulo-ocular function by video and functional Head Impulse Tests (vHIT and fHIT) and their possible correlations with Tinetti Balance Test score. Thirty one patients over 65 years of age admitted with trauma due to falls were recruited. Vestibular evaluation (complete otoneurological assessment, vHIT, fHIT), cognitive tests (Mini Mental State Examination), anxiety and depression evaluation and Tinetti balance test were performed. The possibility of a correlation between the head impulse tests (vHIT, fHIT) and the Tinetti balance test was investigated by logistic regression analysis (Nagelkerke r2 and Wald test). A linear correlation was found between the Tinetti Balance Test score and fHIT, whereas no correlation was found for vHIT. The fHIT is an effective objective test for predicting the risk of falls in elderly patients.